2017
DOI: 10.1038/bjc.2017.57
|View full text |Cite
|
Sign up to set email alerts
|

The PICTURE study: diagnostic accuracy of multiparametric MRI in men requiring a repeat prostate biopsy

Abstract: Background:Transrectal prostate biopsy has limited diagnostic accuracy. Prostate Imaging Compared to Transperineal Ultrasound-guided biopsy for significant prostate cancer Risk Evaluation (PICTURE) was a paired-cohort confirmatory study designed to assess diagnostic accuracy of multiparametric magnetic resonance imaging (mpMRI) in men requiring a repeat biopsy.Methods:All underwent 3 T mpMRI and transperineal template prostate mapping biopsies (TTPM biopsies). Multiparametric MRI was reported using Likert scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 30 publications
5
81
0
Order By: Relevance
“…The goals are not only to stage the disease and to locate and target suspect lesions but also to guide decisions about whether to proceed with a biopsy [4,10]. Unfortunately, the results of some mpMRI studies have been inconclusive, as discussed below.…”
Section: Discussionmentioning
confidence: 99%
“…The goals are not only to stage the disease and to locate and target suspect lesions but also to guide decisions about whether to proceed with a biopsy [4,10]. Unfortunately, the results of some mpMRI studies have been inconclusive, as discussed below.…”
Section: Discussionmentioning
confidence: 99%
“…All prostate tissue was acquired during the PICTURE trial, a paired‐cohort confirmatory study designed to assess the accuracy of mpMRI in detecting clinically significant cancer . For this purpose, 249 men with a previous TRUS biopsy requiring a repeat evaluation underwent a 3T mpMRI followed by TPM biopsies of the entire prostate at 5 mm intervals.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, its accuracy and clinical implications have been questioned by many. [2][3][4] As an attempt to address this concern, the present study assessed the relationship between MRI-based preoperative grading and staging compared to pathologic outcome following radical prostatectomy (RP). The authors found significant discordance in grade group and stage leading to a change in the NCCN risk stratification in 45% of patients, of which 33% would have been in a higher risk group and 12% would have been in a lower risk group based on RP pathology.…”
Section: Editorial Commentmentioning
confidence: 99%
“…First, the accuracy of the fusion biopsy is not sufficient to forego the conventional systematic biopsy at the present time. 2,7 Second, appropriate radiological expertise is critical to the success of the fusion biopsy platform. In this regard, there is concern for a market-driven, rapid implementation of a new technology without the appropriate expertise to optimize the benefit of a new technology.…”
Section: Editorial Commentmentioning
confidence: 99%